A smart ratiometric red fluorescent chemodosimeter for fluoride based on anthraquinone nosylate. (26th May 2017) - Shweta; Kumar, Ajit; Neeraj; Asthana, Sharad Kumar; Upadhyay, K. K.
Abstract : A smart ratiometric red fluorescent chemodosimeter (AH ) has been explored for specific detection of F − with a lowest detection limit of 3.45 × 10 −10 M. The sensing mechanism was worked out as fluoride-triggered deprotonation of imidazole accompanied by deprotection of the nosylate group. Abstract : The present work reports a smart design of a chemodosimeter, namely 4-(6, 11-dihydro-6, 11-dioxo-1 H -anthra[1, 2- d ]imidazol-2-yl)phenyl-4-nitrobenzenesulfonate (AH ), which recognises F − specifically through a naked eye colour change from light yellow to light orange and remarkable ratiometric fluorescence from green to red from the matrix of a large number of similar anions in acetonitrile solution. The sensing mechanism was worked out as fluoride-triggered deprotonation of imidazole accompanied by deprotection of nosylate group ( p -nitrobenzenesulfonate group).AH was fully characterized through single crystal X-ray diffraction studies along with FT-IR, 1 H and 13 C NMR and ESI-MS. The detection limit calculated through fluorescent titration was found to be 3.45 × 10 −10 M. Theoretical calculations at density functional level were in agreement with experimental observations.AH also showed its practical applicability in the form of test paper strips.